Gender Bias in Academic Writing: Challenges and Equity Strategies - Rahman, Muhammad Arinal (Pusat Studi Gender dan Anak Universitas Islam Negeri Antasari Banjarmasin, 2024)
This review synthesizes existing research on the intricate relationship between gender and academic writing, exploring gendered writing styles, perceptions of writing quality, representation in academic publishing, intersectionality with other social identities, and interventions to promote gender equity. Findings reveal nuanced variations in writing practices, with female scholars tending toward more tentative styles and male scholars favoring assertive approaches. Evaluation biases persist, perpetuating gender stereotypes that impact grading and recognition. Structural inequities manifest in academic publishing landscapes, hindering diverse representation. An intersectional lens elucidates the compounding effects of gender, race, class, and disciplinary affiliations. Interventions proposed include gender-neutral guidelines, bias training, diversity initiatives, and institutional policies supporting inclusivity. While progress has been made, ongoing efforts are needed to dismantle persisting biases, address inequities, and cultivate equitable spaces valuing diverse voices in knowledge production. This comprehensive review informs future research directions and institutional strategies toward gender equity in academic writing.